Mythopoeïa: ou l'art de forger les "mythes" dans l'"aire culturelle" syro-mésopotamienne, méditerranéenne et indo-européenne - Pace, Jérôme (Publications of the Foundation for Finnish Assyriological Research, 2018)
A study of religious and historical myths, analyzing several interrelated mythical themes (storm god, young hero, chaos, combat with monsters, kingship, final judgment, organization of the cosmos, and foundation of kingship) encountered in the ancient oikumene extending from the Eastern Mediterranean to India